Corporate shared prosperity: scale development and validation - Hossain, Mohammad Imtiaz; Heng Teh, Boon; Chong, Lee-Lee; Ong, Tze San; Tabash, Mosab I.; Jamadar, Yasmin (Cogent, 2024)
Business organizations are forced to prioritize ensuring corporate shared prosperity (CSP) through enhancing corporate sustainability performance and stakeholder’s betterment. There is a lack of comprehensive and quantifiable measurement of CSP and existing studies are conceptual and case study based. Thus, this study explores the essential dimensions involved in developing and verifying the corporate shared prosperity measurement which will help researchers to conduct empirical study. This scale development paper may prove valuable to both readers and scholars engaged in the field of sustainability and stakeholder development. Stakeholder theory is used as an underpinning theory. Sixteen (16) items under five (5) dimensions were developed to measure corporate shared prosperity after reviewing the existing literature, verifying by focus group discussion, and analyzing 229 Malaysian manufacturing firms responses using exploratory factor analysis and confirmatory composite analysis (CCA). This reliable and valid scale would benefit scholars in measuring CSP and examining the impact of sustainable performance on CSP. Further empirical evaluation based on this developed scale would ensure inclusive, sustainable development for stakeholders and make organizations more resilient. This research is a unique and initial attempt to develop a validated questionnaire survey based tool to measure corporate shared prosperity quantitatively. © 2024 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.